Comparison of the effectiveness of critical thinking training and social cognitive training on the emotional creativity of female students of the first secondary school - Najary Moghadam, Azam; Bagheri, Nasrin; Abolmaali, Khadijeh (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2023)
Background and Aim: In today's world, it is believed that one should have global thinking, but implement these global thoughts locally. This can also be considered as the localization of global thoughts and ideas. The purpose of this research was to compare the effectiveness of critical thinking training and social cognitive training on the emotional creativity of female students of the first secondary school. Methods: The current research method was quasi-experimental with a pre-test-post-test design with a control group and a one-month follow-up, which was conducted in Sabzevar high schools in 2021-22. The statistical population was made up of all the students of the first secondary school age range, who were selected as available and according to the sample size of 98 female high school students. The tools for collecting information were library studies, questionnaires and documents. In the collection of information, a questionnaire measuring emotional creativity was used as a tool. The sampling method in the present study was available by sampling method. The sample size included 66 people, that is, 33 people were considered for each group. In this research, the components and the total score of emotional creativity were the dependent variables, and the information related to them was collected in the three stages of pre-test, post-test and follow-up from the participants of the experimental and control groups, and to test the effectiveness of the implementation of the independent variable on the dependent variable of the method Analysis of variance with repeated measures was used. The software used is SPSS version 26. Results: The difference in the average scores of the components and the total score of emotional creativity in the pre-test-post-test and pre-test-follow-up stages was statistically significant, but the difference in the average scores in the post-test-follow-up stages was not significant. The difference in the mean of the components and the total score of emotional creativity in the two groups of critical thinking and control is statistically significant. The difference in the effect of two methods of social cognitive education and critical thinking on the components of readiness, innovation, effectiveness and the total score of emotional creativity was significant. Conclusion: According to the results of the research, critical thinking and social cognitive training has increased the emotional readiness of female students in the first year of high school. Critical thinking training created a significant difference between the control and experimental groups in terms of the variable of emotional creativity. And critical thinking and social cognitive training has improved innovation in female students of the first year of high school. Teaching critical thinking and social cognition has not had a significant impact on students.